2018
DOI: 10.1080/10705422.2018.1449044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ebbs and Flows of Community Engagement: The Pyramid of Engagement and Water Activism in Two Canadian Communities

Abstract: In this article, we share results from a comparative study exploring the dynamics of community engagement surrounding local water advocacy organizations in two Canadian communities. Although emergent local issues and the perception of crisis triggered some short-term community engagement, social factors such as collective identity, a sense of community, and sense of efficacy appear to be more important for sustaining and deepening engagement. Drawing on the results, we show how the pyramid of engagement, by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The Water Wins team found that the key to sustained community engagement with evidence-based water stewardship was telling stories that focussed on the positives of sustained grassroots action. Such stories gave community members a sense of fulfilment and belonging, and a sense of community efficacy [Case and Zeglen, 2018]. This case emphasises the value of storytelling in mobilising community action and reinforces the benefits of scholars working alongside practitioners to better understand the social contexts and hence the relevance for creating change.…”
Section: Collaboration Creates More Relevant Storytellingmentioning
confidence: 64%
See 1 more Smart Citation
“…The Water Wins team found that the key to sustained community engagement with evidence-based water stewardship was telling stories that focussed on the positives of sustained grassroots action. Such stories gave community members a sense of fulfilment and belonging, and a sense of community efficacy [Case and Zeglen, 2018]. This case emphasises the value of storytelling in mobilising community action and reinforces the benefits of scholars working alongside practitioners to better understand the social contexts and hence the relevance for creating change.…”
Section: Collaboration Creates More Relevant Storytellingmentioning
confidence: 64%
“…The Water Wins team recognised that success stories focussing on what could be achieved through group solidarity were important tactics for these organisations to employ [Case and Zeglen, 2018]. They recommended that community groups focus on building a community base to ease people's anxiety about engaging in controversial policy processes.…”
Section: Collaboration Creates More Relevant Storytellingmentioning
confidence: 99%
“…Creating such a large-scale policy change for infrastructure requires "continuous and deepening levels" of engagement on the issues. [15] Again, as ASCE's experience with its Vision 2025 demonstrates, such initiatives can lose momentum, even perish if ASCE cannot generate and sustain an engaged membership and recruit champions. [15] Achieving large-scale changes in infrastructure policy with civil engineering champions requires ASCE to solve three more subsidiary problems; first, engaging its membership [16] to deepen the pool of leaders in ASCE membership; secondly, repositioning the profession to focus on building social capital, not social licenses and lastly, achieving "critical mass," i.e., mobilizing a sufficient number of these champions who can collectively work to bring about large-scale policy changes.…”
Section: The Problem Of Recruiting Championsmentioning
confidence: 99%
“…[16] These frameworks can take various forms, such as the ladder of participation or the ladder of engagement. [15] "These models depict lower-order forms of participation on its lower levels and progressively more intensive forms of engagement as one moves up towards more leadership-oriented roles…. (focusing on) … roles and commitment levels rather than degrees of access to decision-making power."…”
Section: An Integrated Vision Of Management and Leadership For Delivering 21st-century Civil Infrastructurementioning
confidence: 99%
See 1 more Smart Citation